Aluminium, carbonyls and cytokines in human nipple aspirate fluids: Possible relationship between inflammation, oxidative stress and breast cancer microenvironment - Mannello, F.; Ligi, D.; Canale, M. (Journal of inorganic biochemistry, 2013)
The human breast is likely exposed to Al (aluminium) from many sources including diet and personal care products. Underarm applications of aluminium salt-based antiperspirant provide a possible long-term source of exposure, especially after underarm applications to shaved and abraded skin. Al research in breast fluids likely reflects the intraductal microenvironment. We found increased levels of aluminium in noninvasively collected nipple aspirate fluids (NAF) from 19 breast cancer patients compared with 16 healthy control subjects (268 vs 131μg/l, respectively; p<0.0001). In the same NAF samples we found significantly increased levels of protein oxidative carbonyls in cancer patients compared to healthy women (2.35 vs 0.41nmol/mg prot, respectively; p<0.0001). Aluminium content and carbonyl levels showed a significant positive linear correlation (r2 0.6628, p<0.0001). In cancer NAF samples (containing higher amounts of aluminium salts) we also found a significantly increased levels of pro-inflammatory cytokines (IL-1β, IL-6, IL-12 p70, and TNF-α) and chemoattractant CC and CXC chemokines (IL-8, MIP-1α and MCP-1). In 12 invasive cancer NAF samples we found a significant positive linear correlation among aluminium, carbonyls and pro-inflammatory IL-6 cytokine (Y=64.79x−39.63, r2 0.8192, p<0.0005), as well as pro-inflammatory monocyte chemoattractant MCP-1 cytokine (Y=2026x−866, r2 0.9495, p<0.0001). In addition to emerging evidence, our results support the possible involvement of aluminium ions in oxidative and inflammatory status perturbations of breast cancer microenvironment, suggesting aluminium accumulation in breast microenvironment as a possible risk factor for oxidative/inflammatory phenotype of breast cells. Analyzing breast fluids mirroring intraductal microenvironment, we found in cancer samples (containing higher amounts of aluminium and oxidative products) significantly increased and correlated levels of pro-inflammatory (like IL-6) and chemoattractant cytokines (like MCP-1). We suggest aluminium accumulation in breast microenvironment as possible risk-factor for oxidative/inflammatory phenotype of breast cells. [Display omitted] •Relationships among aluminium, oxidation and cytokines in breast microenvironment.•Aluminium measurement in nipple aspirate fluids from healthy and cancer patients.•Correlation among cytokines, protein carbonyl and aluminium in breast cancer fluid.•Influence of aluminium on breast cancer oxidative and inflammatory pathways.